Performance of Trichoderma Harzianum Rifai as a Biological Control Agent for Basal Stem Rot of Oil Palm (Elaeis Guineensis Jacq.) Caused by Ganoderma Boninense Pat - Sundram, Shamala (2005)
Basal stem rot (BSR) is a major threat to the oil palm industry. The disease is caused by Ganoderma boninense, which rots the internal tissues at the trunk base resulting in stem fracture and death of palm. The present study investigated the efficacy of two isolates of Trichoderma harzianum (BIO T32 and BIO T66) as potential biological control agents against BSR based on in vitro and in vivo trials. The study revealed that treatment applied as a soil drench using conidial suspension (mean of 1.61 x lo8 sporeslml) of BIO T32 in addition to a Trichoderma-incorporated palm press fibre (ppf) surface mulch, performed better with a significant difference compared to the use of BIO T66. The disease severity index (DSI) of the former was 28.35 compared to 76.67 of the latter. BIO T32 was also a competent biological control agent in the delayed treatment given to pre-infected seedlings at 6 weeks before treatment with BIO T32, giving a DSI of 45, which was statistically significant compared to the infected and untreated control seedlings with a DSI of 86.67. In testing the synergistic effect by combining the 2 isolates, a poorer performance was observed based on the DSI and plant biomass compared to single application of BIO T32. Isolate BIO T66 which showed good antagonistic properties in the in vitro assessment was not found to display similar results in the in vivo trials. A series of treatments were evaluated for their potential as a BIO T32 carrier. Out of the 3 studies, only ppf and compost exhibited promising results in their capacity as surface 4 mulches, where treatments with either one gave a DSI of 30. Both are food base carriers for they increased the growth of oil palm seedlings significantly, with compost displaying better results. Treatment with compost in terms of vegetative growth gave the highest plant biomass, leaf area measurement, nitrogen, phosphorus and potassium (NPK) content in the seedlings compared to the other 2 treatments of ppf and the untreated control seedlings. 1 In total, the experiment revealed that the application of BIO T32 as a single inoculum was the best treatment, giving a DSI of 28.35. Trials using a single application of BIO T66 and BIO T66 mixed with BIO T32 performed poorly, giving a DSI of 76.67 each and were not significantly different from the infected non-treated control plants. An appropriate interval of conidial suspension's application played a pertinent role in the inhibition of disease as demonstrated in the delayed treatment. The application of compost was found to be an interesting alternative to ppf as surface mulch, which functions also as a Trichoderma carrier. Finally, in terms of vegetative growth both ppf and compost as food base carriers significantly increased plant biomass, total leaf area measurement and N uptake compared to the untreated control.